2015
DOI: 10.1309/ajcpwe2hbfcgdids
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Identification of Immunophenotypically Aberrant T-Cell Clusters on Skin Shave Biopsy Specimens From Patients With Mycosis Fungoides

Abstract: FC is capable of identifying putative neoplastic cells on SSB specimens from patients with MF. Bright homogeneous CD26 expression is a common and previously undescribed immunophenotypic aberrancy on MF skin infiltrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…CD26 overexpression was previously described in 30–73% of MF cases . We demonstrated that CD26 expression is related to different outcomes (secondary SS or t‐MF) with CD26‐negative expression related to a high risk of progression.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…CD26 overexpression was previously described in 30–73% of MF cases . We demonstrated that CD26 expression is related to different outcomes (secondary SS or t‐MF) with CD26‐negative expression related to a high risk of progression.…”
Section: Discussionsupporting
confidence: 60%
“…In our series, a loss of surface CD3 expression or CD3 dim was found in 44% (12/27) of cases. Abnormal CD3 dim was previously described in SS and MF skin biopsies in 55–72% of cases. Other notable changes in pan‐T antigen in this series were a loss of or diminished expression of CD7 in 92.6% (25/27) of cases and a loss of CD2 described in 20% of SS cases and 11% (3/27) of cases of this series .…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…10 The T-LPDs may be set in a polymorphic inflammatory background with eosinophils, neutrophils, plasma cells, and histiocytes similar to mixed cellularity or nodular sclerosis-type CHL. In addition, the RSC-like cells can coexpress CD30 (Figure, F), CD15, and PAX5, whereas CHL may have aberrant T-antigen expression and is CD15 À in a subset of cases.…”
Section: Flow Cytometrymentioning
confidence: 99%